2021
DOI: 10.1016/j.hlpt.2020.10.016
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 on Instagram: A content analysis of selected accounts

Abstract: Objective This study aimed to characterize the representation of public health information related to COVID-19 posted on Instagram in 2020. Methods This qualitative content analysis study was conducted in Iran as one of the countries with the highest number of confirmed cases of COVID-19. Data were collected from the contents published from February 19 to April 3, 2020, on Instagram. The search feature of the Instagram app was used to find the posts related to Coronavir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 20 publications
1
45
0
9
Order By: Relevance
“…The study by Niknam et al (2021) 23 on the analysis of the Instagram content about COVID-19 revealed that the post mostly contained information about the following: drug treatment, distribution of medications, news about vaccines, symptoms, and characteristics of the virus. With this, it is perceived that Instagram also has a system for dissemination and sharing, evidenced by its metrics, information that allows for fast reach, verifying the subject matter being shared, and the reactions to it by the readers.…”
Section: Content and Analysis Of The Information Included In The Postsmentioning
confidence: 99%
“…The study by Niknam et al (2021) 23 on the analysis of the Instagram content about COVID-19 revealed that the post mostly contained information about the following: drug treatment, distribution of medications, news about vaccines, symptoms, and characteristics of the virus. With this, it is perceived that Instagram also has a system for dissemination and sharing, evidenced by its metrics, information that allows for fast reach, verifying the subject matter being shared, and the reactions to it by the readers.…”
Section: Content and Analysis Of The Information Included In The Postsmentioning
confidence: 99%
“…Politicians were able to use the content of their networks to promote public participation in the prevention of and the fight against the pandemic (Niknam et al, 2020;Castillo-Esparcia, Fernández-Souto and Puentes-Rivera, 2020). Research, such as a study of the use of Twitter as a presidential communication channel in the initial period of COVID-19 (Manfredi-Sánchez et al, 2021), indicated Presidents Sánchez and Bolsonaro deployed a health management communication strategy, while López Obrador and Fernández paid little attention to health policy.…”
Section: Instagram and Covid-19 In Latin Americamentioning
confidence: 99%
“…The objective of this research was to study the multimodal narrative of candidates and to determine whether it carried implicit misinformation in the coherence of the coronavirus prevention discourse with respect to the images and text projected by candidates on their Instagram accounts. Analyzing the content of Instagram posts can help identify the thoughts and feelings of the candidates in the face of the health crisis (Niknam et al, 2020).…”
Section: Misinformation In Multimodal Discoursementioning
confidence: 99%
“…One of the social media that can be used as a channel to convey crisis information is Instagram, where Niknam et al, (2020), found that Instagram users used various strategies in creating content about the public health crisis during the Covid-19 pandemic, and generated as many as 23 themes on their content posts which include epidemiology and statistics, training and care, general prevention guidelines, hygiene, healthy diet and lifestyle, patients, diagnosis and treatment, personal protective equipment, traditional medicine, psychology, children, cultural aspects, socio-cultural impact, religion, misinformation and wrong behavior, animals, satire, health care system condition, politics, quarantine, economic impact, and world news. Such information is certainly very much needed with credible sources, which can be provided by interested organizations.…”
Section: Literature Reviewmentioning
confidence: 99%